Body size and weight, and the nutrition and activity behaviours of sexual and gender minority youth: findings and implications from New Zealand. Issue 13 (4th June 2019) - Lucassen, Mathijs FG; Guntupalli, Aravinda Meera; Clark, Terryann; Fenaughty, John; Denny, Simon; Fleming, Theresa; Smith, Melody; Utter, Jennifer
Abstract: Objective: To describe the body size and weight, and the nutrition and activity behaviours of sexual and gender minority (SGM) students and compare them with those of exclusively opposite-sex-attracted cisgender students. Male and female SGM students were also compared. Design: Data were from a nationally representative health survey. Setting: Secondary schools in New Zealand, 2012. Participants: A total of 7769 students, 9 % were SGM individuals. Results: Overall, weight-control behaviours, poor nutrition and inactivity were common and, in many cases, more so for SGM students. Specifically, male SGM students (adjusted OR; 95 % CI) were significantly more likely to have tried to lose weight (1·95; 1·47, 2·59), engage in unhealthy weight control (2·17; 1·48, 3·19), consume fast food/takeaways (2·89; 2·01, 4·15) and be physically inactive (2·54; 1·65, 3·92), and were less likely to participate in a school sports team (0·57; 0·44, 0·75), compared with other males. Female SGM students (adjusted OR; 95 % CI) were significantly more likely to engage in unhealthy weight control (1·58; 1·20, 2·08), be overweight or obese (1·24; 1·01, 1·53) and consume fast food/takeaways (2·19; 1·59, 3·03), and were less likely to participate in a school sports team (0·62; 0·50, 0·76), compared with other females. Generally, female SGM students were more negatively affected than comparable males, except they were less likely to consume fast food/takeaways frequently (adjusted OR; 95 % CI: 0·62; 0·40, 0·96). Conclusions: SGM students reported increased weight-control behaviours, poor nutrition and inactivity. Professionals, including public health nutritionists, must recognize and help to address the challenges facing sexual and gender minorities.